THE SUPREME COURT'S AUTHORITY AS AN IMPLEMENTER OF INDEPENDENT JUDICIAL POWER IN THE RECRUITMENT OF JUDGES - Teguh, Pri Pambudi; Bachmid, Fahri; Rumadhan, Ismail (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2022)
The primary issue addressed in this study is how the Supreme Court's authority is autonomous in hiring judges with the status of state officials for judicial organizations within its jurisdiction. Because the legislation was the primary source of information, this study took a normative juridical approach. The study's findings indicate that the current legal framework is not yet fully capable of accurately regulating, thoroughly implementing, and enforcing the judicial system and pattern and judges' status as state officials. The current system and pattern of judicial recruitment continue to demonstrate the lack of transparency and uncertainty regarding the legal rules governing the recruitment pattern of judges with state official status. The existing rules retain a tenuous legitimacy because they are not governed by the Constitution, which establishes an independent Judicial Authority charged with enforcing law and justice. As a result, it will be required to enact new rules and regulations governing the system and pattern of recruitment of judges in accordance with the characteristics of judges' positions as state officials in the future to ensure the implementation and accountability of judicial responsibilities.